Javier María Donézar Díez de Ulzurrun - Layana Ilundáin, César (Huarte de San Juan. Geografía e Historia, 2014)
Javier Donézar Díez de Ulzurrun is one of the first Navarre’s Contemporary History specialists in pioneering the renewal approach to Spanish historiography in the early sixties. He’s renowned by his empiric study of the land ownership transformations during the Old Regime crisis. His doctoral thesis on the Disentailment of Mendizabal in Navarre enabled to get a closer view to the raise of the agricultural bourgeoisie in Navarre. Later on, he lead a pioneering investigation on the agrarian structures during the Old Regime through the emptying of the «Respuestas particulares» (individual answers) provided by the Cadastre of La Ensenada for the vast province of Toledo, which lead to a pioneering use of computer science in Historiography research. Furthermore, he’s also addressed other historical topics, such as the liberal society and nationalism, and has contributed to the spread of historiography in historical works, university handbooks, and articles in several specialized magazines.